1984
DOI: 10.1021/bi00319a016
|View full text |Cite
|
Sign up to set email alerts
|

A specific subunit of vitellogenin that mediates receptor binding

Abstract: Vitellogenin, an estrogen-induced serum protein synthesized in the liver, is composed of two Mr 250K polypeptides. It is specifically transported by a receptor-mediated endocytic process into the developing oocytes of virtually all oviparious animals. Following endocytosis, in the chicken, vitellogenin is specifically processed to yield several smaller products including the phosvitins (PV) and the lipovitellins (LV). These products are then stored within the oocyte until they are degraded during embryogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 34 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…In the last decade, detailed information on the VTG receptors has been accumulated for birds, Gallu.s domesticus (Woods and Roth, 1984;Stifani et al, 1988Stifani et al, , 1990bBarber et al, 1991;Schneider, 1992;Shen et al, 1993;Bujo et al, 1994;Lachlan et al, 1994), amphibians, Xenopus laevis (Opresko and Wiley, 1987;Stifani et al, 1990b) and invertebrates (Rohrkasten and Ferenz, 1986;Hafer and Ferenz, 1991;Sappington et al, 1995 (Selman and Wallace, 1982).…”
mentioning
confidence: 99%
“…In the last decade, detailed information on the VTG receptors has been accumulated for birds, Gallu.s domesticus (Woods and Roth, 1984;Stifani et al, 1988Stifani et al, , 1990bBarber et al, 1991;Schneider, 1992;Shen et al, 1993;Bujo et al, 1994;Lachlan et al, 1994), amphibians, Xenopus laevis (Opresko and Wiley, 1987;Stifani et al, 1990b) and invertebrates (Rohrkasten and Ferenz, 1986;Hafer and Ferenz, 1991;Sappington et al, 1995 (Selman and Wallace, 1982).…”
mentioning
confidence: 99%
“…In contrast to the invertebrate vitellogenin, vertebrate vitellogenin (phosvitin) is a sialoglycoprotein containing a single high-mannose N-linked oligosaccharide species (Shainkin and Perlmann, 1971a). Competition studies indicate that the phosvitin portion of vitellogenin molecule mediates the binding and uptake (Woods and Roth, 1984). However, no report is available on the oligosaccharide component of the crustacean vitellogenin/vitellin.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to its Zn-chelating activity, OP has been employed as a probe to determine the importance of Zn as a functional component of metalloproteins (Woods and Roth 1984;Wang and Jeng 2006). Identification of the 30-and 35-kDa polypeptides as homologs of the Lv1 domain of zfVg1 correlated well with the metal-dependent, UV-damaged-DNA binding activities of the two molecules (Lai et al 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Analysis of UV damage DNA-binding activity in fractionated zebrafish extracts showed that proteins interacting preferentially with 6-4PPs were effectively separated from nonspecific binding proteins due to In oviparous vertebrates, Vgs are produced in the liver in response to estrogen stimulation. After secretion to the blood, these metalloproteins are taken up from the plasma by developing oocytes via receptormediated endocytosis and are cleaved into three portions-lipovitellin I (Lv1), phosvitin (PV), and lipovitellin II (Lv2) (Woods and Roth 1984;Montorzi et al 1995;Falchuk and Montorzi 2001). As a metalloprotein, the 220-kDa Vg of the frog Xenopus laevis was shown to carry different metals at varied levels.…”
Section: Discussionmentioning
confidence: 99%